Anti-osteoclastic effects of C-glucosidic ellagitannins mediated by actin perturbation - Georgess, Dan (2018)
Actin subunits assemble into actin filaments whose dynamics and three-dimensional architectures are further regulated by a variety of cellular factors to establish the functional actin cytoskeleton. The C-glucosidic ellagitannin vescalagin and its simpler analogue vescalin, affect both the dynamics and the ultrastructure of the actin cytoskeleton by directly binding to F-actin. Herein, we show that in vitro, the two compounds induce the formation of distinct F-actin networks characterized by different superstructures and dynamics. In living mature osteoclasts, highly specialized bone-degrading cells that constantly remodel their cytoskeleton, vescalagin and vescalin alter actin dynamics at podosomes and compromise the integrity of the podosome belt that forms the bone-degrading apparatus. Both compounds target the bone-resorbing activity at concentrations that preserve osteoclastic maturation and survival and with no detectable impact on the behaviour of bone-forming osteoblastic cells. This anti-osteoclastic activity of vescalagin and vescalin reveals the potential of targeting actin dynamics as a new therapeutic opportunity and, in this case, as a plausible approach for the local treatment of osteoporosis.